Biochar amendment reduces cadmium uptake by stimulating cadmium-resistant PGPR in tomato rhizosphere. (November 2022) - Zhou, Xingang; Zhang, Xianhong; Ma, Changli; Wu, Fengzhi; Jin, Xue; Dini-Andreote, Francisco; Wei, Zhong
Abstract: Biochar amendment in the soil can exert a positive effect in reducing heavy metal toxicity in plants. However, it remains unclear the extent to which this effect is associated with the modulation of plant growth-promoting rhizobacteria (PGPR). Here, we initially conducted a pot experiment using tomato ( Solanum lycopersicum L.) as a model plant grown in soil spiked with cadmium. First, we found biochar amendment to result in reduced cadmium uptake in tomato plants and trackable changes in the tomato rhizosphere microbiome. Then, a rhizosphere transplant experiment validated the importance of this microbiome modulation for cadmium-toxicity amelioration. Sequence-based analyses targeted the isolation of representative isolates of PGPR, including Bacillus and Flavisolibacter spp. that displayed in vitro cadmium tolerance and biosorption capabilities (in addition to abilities to solubilize phosphate and produce indole acetic acid). Last, we performed a soil inoculation experiment and confirmed the effectiveness of these isolates in reducing cadmium toxicity in tomato plants. Besides, we found the inoculation of these taxa as single inoculant and in combination to result in increased activities of specific antioxidant enzymes in tomato tissues. Taken together, this study revealed the ecological and physiological mechanisms by which biochar amendment indirectly alleviate cadmium toxicity in tomato plants, in this case, via the modulation and activity of specific PGPR populations. This study provides new insights into strategies able to promote beneficial PGPR in the rhizosphere with potential application to ameliorate heavy metal toxicity in plants. Graphical abstract: Image 1 Highlights: Biochar enhances tomato plant growth and reduces cadmium toxicity. Changes in rhizosphere microbiome contribute to reduced cadmium uptake. Biochar amendment stimulates plant growth-promoting rhizobacteria. Bacterial taxa associated with cadmium biosorption are enriched by biochar.